2016
DOI: 10.1080/19425120.2016.1167793
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Factors Influencing the Length, Compensatory Growth, and Size‐Selective Mortality of Juvenile Bristol Bay, Alaska, Sockeye Salmon at Sea

Abstract: The productivity of Bristol Bay, Alaska, Sockeye Salmon Oncorhynchus nerka increased during the mid‐1970s. This increase is believed to be partially due to an increase in early marine growth associated with the 1976–1977 cool‐to‐warm shift in summer sea surface temperature (SST). The body size of juvenile salmon during their first year at sea is believed to regulate their ability to survive over winter. The back‐calculated smolt length, first‐year ocean growth, and total juvenile length of Sockeye Salmon from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Thus it is unclear if a relatively constant size after one year of ocean rearing is indeed evidence for size-selective mortality, or simply a manifestation of compensatory growth rate. Yamusiishi et al [ 33 ] reported both compensatory growth and size-selective mortality for Bristol Bay sockeye salmon, but the magnitude of size-selective mortality relative to total mortality was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it is unclear if a relatively constant size after one year of ocean rearing is indeed evidence for size-selective mortality, or simply a manifestation of compensatory growth rate. Yamusiishi et al [ 33 ] reported both compensatory growth and size-selective mortality for Bristol Bay sockeye salmon, but the magnitude of size-selective mortality relative to total mortality was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Recent warming of the southeastern Bering Sea was accompanied by increased returns of Bristol Bay sockeye salmon. Relative abundance and growth rates of juvenile Bristol Bay sockeye salmon were shown to be high during warm years (Farley and Trudel 2009;Yasumiishi et al 2016). Yasumiishi et al (2016) reported that the total length of juvenile sockeye salmon during the first ocean year increased with summer SST in the eastern Bering Sea, suggesting a possible mechanism for increased abundance of Bristol Bay sockeye salmon.…”
Section: Influence Of Climate-ocean Conditions On Biological Parameters Of Salmonmentioning
confidence: 99%
“…Relative abundance and growth rates of juvenile Bristol Bay sockeye salmon were shown to be high during warm years (Farley and Trudel 2009;Yasumiishi et al 2016). Yasumiishi et al (2016) reported that the total length of juvenile sockeye salmon during the first ocean year increased with summer SST in the eastern Bering Sea, suggesting a possible mechanism for increased abundance of Bristol Bay sockeye salmon. They hypothesize that there is a trade-off between increased length and reduced energetic status of sockeye salmon in warming climate regimes, which may affect their survival.…”
Section: Influence Of Climate-ocean Conditions On Biological Parameters Of Salmonmentioning
confidence: 99%
“…Previous studies have suggested that environmental and ecological factors should be accounted for in order to better understand the behavior of fish stocks and more accurately assess population levels (Garcia and Cochrane 2005; Lehodey et al 2006; Methot 2015; ASMFC 2016, 2017c). Environmental processes, such as El Niño and La Niña in the Pacific Ocean and the North Atlantic Oscillation (NAO) and Atlantic Multidecadal Oscillation (AMO) in the Atlantic Ocean, vary over large spatiotemporal scales, causing varying responses among fish growth rates (Fiedler et al 1986; Otterson et al 2001; Jonsson and Jonsson 2004; Izzo and Zydlewski 2017), predation (Stenseth et al 2002; Nye et al 2009; Yasumiishi et al 2016), recruitment, and other population dynamics (Hare and Able 2007; Nye et al 2009, 2014; Edwards et al 2013; Large et al 2013; Harris et al 2014; Buchheister et al 2016). Climatic processes have been linked to changing physiochemical properties in estuaries (Irby et al 2018) which can have confounding effects on the fish species that rely on certain conditions seasonally within estuaries to survive (Barletta et al 2005).…”
mentioning
confidence: 99%
“…Successful recruitment of young-of-the-year (age-0) fishes has been linked to environmental processes (e.g., Boehlert and Mundy 1988;Hare and Govoni 2005;Lehodey et al 2006;Cury et al 2008). Previous studies have shown that nekton size (Hale and Targett 2018), temperature (Witting et al 1999;Lankford and Targett 2001;Hare and Able 2007;Carassou et al 2011;Yasumiishi et al 2016), salinity (Lankford and Targett 1994;Able et al 2009), freshwater input (Reist et al 2006;Carassou et al 2011), flow (Dunning et al 2009), and wind speed and direction (Nye et al 2014;Schieler et al 2014) can significantly affect transport, growth, and survival of multiple life stages of marine nekton. The NAO and AMO have been linked to trends in fisheries production, distribution, and abundance (Lehodey et al 2006).…”
mentioning
confidence: 99%